Enhanced carbon and nitrogen removal in an integrated anaerobic/anoxic/aerobic-membrane aerated biofilm reactor system. Issue 48 (4th August 2020) - Sun, Zhiye; Li, Mei; Wang, Guofeng; Yan, Xiaojun; Li, Yi; Lan, Meichao; Liu, Rukang; Li, Baoan
Abstract : A pilot-scale anaerobic/anoxic/aerobic-membrane aerated biofilm reactor (A 2 /O-MABR) system was constructed to enhance carbon and nitrogen removal. Abstract : A pilot-scale anaerobic/anoxic/aerobic-membrane aerated biofilm reactor (A 2 /O-MABR) system was constructed to enhance carbon and nitrogen removal. The effects of major operating parameters including the nitrate recycling ratio ( R ), sludge recycling ratio ( r ), and aerobic tank dissolved oxygen (DO) concentration on the system performance were investigated. The average removal efficiencies of the chemical oxygen demand (COD), ammonium nitrogen (NH4 + -N), and total nitrogen (TN) were 89.0 ± 3.2%, 98.8 ± 1.3%, and 68.5 ± 4.2%, respectively, and their effluent concentrations were averagely 22.6 ± 7.3, 0.32 ± 0.2, and 13.3 ± 1.2 mg L −1 . The suspended sludge and biofilm in aerobic tank facilitated the simultaneous nitrification and denitrification (SND) processes. Indeed, unique biofilm layered structure and abundant microbial community in the biofilm on MABR would enhance nitrogen removal. Compared with the A 2 /O system, the A 2 /O-MABR system exhibited higher nitrifying bacteria oxygen uptake rate (OUR) of 58.1 and 54.5 mgO2 per gMLSS per h in suspended sludge and biofilm, respectively, and the lower mixed liquor suspended solid (MLSS) concentration of 1800 mg L −1 . Moreover, high-throughput sequencing indicated that putative nitrogen removal bacteria such as Thauera and Paracoccus could be effectively enriched in the biofilm. Since the volume proportions of the anaerobic, anoxic, aerobic and settling tank in the existing A 2 /O system of the WWTP was not changed, the A 2 /O-MABR system was simple and practical for the upgrading of A 2 /O system.